Arrangement and localization of the human GM-CSF receptor α chain gene CSF2RA within the X-Y pseudoautosomal region - Rappold, Gudrun; Willson, Tracy A.; Henke, Anja; Gough, Nicholas M. (Genomics, 1992)
The gene encoding one subunit of the receptor for the hemopoietic growth factor, GM-CSF, has been previously localized to the short arm of the human sex chromosomes. By pulsed-field gel electrophoresis, the precise localization of this gene, CSF2RA, within the pseudoautosomal region has been determined. The gene is located 1180 to 1300 kb from the telomere, in close proximity to the CpG island B5. The CSF2RA gene spans at least 45 kb, and a representation of most of the gene on three overlapping cosmid clones has been obtained. The exon(s) encoding the first 35 bp of cDNA sequence lies outside these cosmids. The CSF2RA gene is characterized by abundant hypervariable sequences, and a number of informative restriction fragment length polymorphisms have been defined.
Online 25 July 2005
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 31.03.2021